PENGARUH LIKUIDITAS, RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM (STUDI PADAiPERUSAHAAN MANUFAKTURiSUBiSEKTORsANEKApINDUSTRI1YANG TERDAFTAR$DI BEI!PERIODE 2015-2018) - Muchamad Arifin; Rispantyo Rispantyo; Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The stock price has become an important thing in the economy especiallyin the capital market. This study was conducted to test whether liquidity, return onequity and earnings per share significantly affect the stock price in themanufacturing industry of various industry sub-sectors. Thisistudy uses secondarydata in the form of audited financial statements originating from the IndonesiaStock Exchange (IDX). The population in this study is the manufacturingcompanies of various industrial subsectors during the 2015-2018 observationperiod. The sampling technique in this study used a purposive sampling method.Data analysis techniques used in this study were descriptive analysis, classicassumption test, linear regression analysis test, hypothesis testing (F test and Ttest) and coefficient of determination. Based on the results of data analysis theeffect of Liquidity does not have a significant effect on stock prices, Return onequity does not have a significant effect on stock prices and Earning per share hasa significant effect on stock prices.